Penerapan Canva Pada Mata Pelajaran IPA di Sekolah Dasar Kelas 5 Rambatan pada Era Revolusi Industry 4.0 - Mekariani Mekariani; Adam Mudinillah (Elementar : Jurnal Pendidikan Dasar, 2021)
In the application of Canvca on science subjects in elementary school and during the 4.0 industrial revolution, it is very sustainable or related because during the era of..In this industrial revolution 4.0 technology is prioritized. To achieve a science learning goal in elementary school, we need to use technology in the form of the Canva application in making learning media. In science learning, this Canfa application is called the parent or stone tool for powereducators to teach science learning materials in grade 5 such as those related to humans, animals and inanimate objects that are around our environment. This data was obtained through qualitative research where data was obtained by direct observationas well as opinions from several people who play an important role in educational institutions. And the results of this research can be used as a basis or example which will refer to the benefits of applying Canva to science subjects in elementary schools during the industrial reform 4.0 period.Keywords:Canva,Elementary School,Science Lessons.